Croatian derivational patterns in Nooj - Srebačić, Matea (Array, 2015)
The paper deals with derivational patterns in Croatian, a Slavic language with rich inflectional and derivational morphology. So far computational processing of Croatian morphology was predominately oriented towards inflectional phenomena. We briefly present CroDeriV, a newly developed resource for processing of derivational phenomena, contains 14 300 Croatian verbs in infinitive form. The paper deals with the rule- based extension of detected derivational families with lemmas of other parts of speech (nouns, adjectives and, adverbs etc.) developed and applied in Nooj. Derivational processes in Croatian refer to compounding and affixation. The affixation encompasses prefixation and suffixation.